Effectiveness of Nano Silver Sulfadiazine and Silver Sulfadiazine on the Growth of Germ Colonies in Deep Dermal Burns - Ronald Gestano; Iqmal Parlianta (Sriwijaya Journal of Surgery, 2019)
ABSTRACT Introduction. Secondary infection is one of the most serious complications and the leading cause of death in burn patients. Silver sulfadiazine (SSD) is the standard topical antimicrobial for burns for the past several decades. At present, nano sized silver particles in sulfadiazine nano silver packages have a high surface to volume ratio and remain effective in low concentrations and minimize silver toxicity to tissues. Methods. This study was a prospective parallel open-label randomized controlled clinical trial. This research was conducted in the Plastic Surgery Subdivision of the Muhammad Hoesin General Hospital Palembang Section from May to September 2018. Deep-dermal burn patients were given random therapy of sulfadiazine and silver sulfadiazine nanosilver. Examination of the number of pre-treatment and post-treatment burn colonies was carried out at the Microbiology Laboratory of Muhammad Hoesin Hospital Palembang. Results. Profile of patients with deep-dermal burns at RSMH are male (76.7%), age group between 15-54 years (66.7%), employees (30%), burn area <20% (66.7 %), and caused by fire (56.7%). There were differences in the mean number of pre and post-treatment colonies in the sulfadiazine nanosilver group, but there were no differences in the mean number of pre-and post-treatment colonies in the silver sulfadiazine group. The mean number of post-treatment colonies in the sulfadiazine nanosilver group was lower than the silver sulfadiazine group, but there were no significant differences in the number of germ colonies in the two groups. Conclusion. Sulfadiazine nanosilver is effective in reducing the number of germ colonies in patients with deep-dermal burns compared to silver sulfadiazine.